Certified community forests positively impact human wellbeing and conservation effectiveness and improve the performance of nearby national protected areas. Issue 6 (27th July 2021) - Loveridge, Robin; Sallu, Susannah M; Pfeifer, Marion; Oldekop, Johan A; Mgaya, Mercy; da Silva, Daniel A; Latham, Julia; Platts, Philip J; Marshall, Andrew R
Abstract: Community forests (CFs) aim to improve human wellbeing and conservation effectiveness, though their performance remains contested. A recent innovation in protected area (PA) governance is to combine CFs with forest certification. We assess (1) the impact of certified CFs on wellbeing and conservation effectiveness; (2) gender inequality and elite capture; (3) interaction effects with neighboring national PAs. We used a novel approach that integrates field data consisting of locally identified indicators representative of multidimensional wellbeing, with remotely sensed data on conservation effectiveness and statistical matching to improve causal inference. We found that CFs positively impacted wellbeing, conservation effectiveness, and reduced gender inequality, though they did not reduce elite capture. We also detected positive interaction effects between certified CFs and neighboring national PAs. Our findings suggest that locating contrasting local and national PA governance approaches next to each other may help to maximize wellbeing and conservation benefits within complex multiuse landscapes.